Submarine Deposition of a Subaerial Landslide in Taan Fiord, Alaska. Issue 10 (11th October 2018) - Haeussler, P. J.; Gulick, S. P. S.; McCall, N.; Walton, M.; Reece, R.; Larsen, C.; Shugar, D. H.; Geertsema, M.; Venditti, J. G.; Labay, K.
Abstract: A large subaerial landslide entered Taan Fiord, Alaska, on 17 October 2015 producing a tsunami with runup to 193 m. We use LiDAR data to show the slide volume to be 76 + 3/−4 million cubic meters and that 51, 000, 000 m 3 entered Taan Fiord. In 2016, we mapped the fjord with multibeam bathymetry and high‐resolution seismic data. Landslide and postlandslide deposits extend 6 km downfjord, are up to 70 ± 11 m thick, and have a total volume of 147, 000, 000 m 3 . Seismic data image a blocky landslide unit and two units deposited immediately after the landslide. The blocky landslide unit is 65, 000, 000 m 3 . We infer it consists dominantly of subaerially derived material and secondarily of fjord floor sediment. The overlying units are likely megaturbidites presumably deposited within minutes to days after the landslide. We infer that these deposits dominantly consist of fjord floor material mobilized and suspended as the slide entered and traveled downfjord. The lower postlandslide unit is up to 35 ± 6 m thick, and the upper unit is up to 12 ± 3 m thick. These deposits are distinctive and will leave a lasting record of the event. This subaerial‐to‐submarine landslide deposit is distinct from other submarine landslide deposits studied in Alaskan fjords because it has a much greater thickness, larger and more angular blocks, distinctive postlandslide megaturbidites, and a higher‐amplitude acoustic signature of the blocky deposit. The tight constraints on the landslide source and deposit volumes, topography, bathymetry, and tsunami runup heights and flow directions should make this a benchmark site for landslide‐tsunami models. Plain Language Summary: A giant landslide fell into Taan Fiord, Alaska, on 17 October 2015 and caused a tsunami that ran up 193 m—the fourth highest ever recorded. All 10 of the highest tsunami runups ever recorded were caused by this mechanism of a landslide entering a water body. These events are rare; most occurred more than 60 years ago, and the physical environment before and after the landslide are generally not well documented. In Taan Fiord, Alaska, we collected excellent postlandslide data of the Earth's surface, both above and below sea level. We are able to calculate the volume of the landslide and the volume that entered the fjord. We are able to image the landslide and postlandslide deposits, on and beneath the fjord bottom, up to 6 km away from where it entered the water. These deposits are distinctive in their character, up to 70 m thick, and we anticipate that other such deposits should be recognizable in other fjords. The careful documentation of the physical environment of the fjord before and after the landslide, combined with tsunami runup and flow directions, should make this a place where tsunami modelers can test their models to see if they work correctly. Key Points: The Taan Fiord, Alaska, landslide and deposit volumes are tightly constrained, making this a benchmark subaerial‐to‐submarine landslide We image a blocky landslide deposit on the fjord bottom, which generated a megaturbidite similar to the volume that entered the fjord This subaerial‐to‐submarine landslide deposit has unique characteristics that should allow identification of other such landslides elsewhere